Current Economic Slowdown and Opportunities for Cost Effective Services and Products using Technological Inventions: An Empirical Study - Tiwari, Tripti; Tiwari, Mohit (International Journal of Economics and Financial Issues, 2020)
Technology has always played a great role in transforming economy. From computers to Internet of Things, the technology has not only supported the business and allied areas but also has revived the economy from time to time. The current economic slowdown has raised the eyebrows of all the industry experts and economics. There has been a major impact on GDP, export growth rate and many other aspects of the economy. The slowdown has come into phases, which may be considered as the result of GST (Goods and Services Tax), Demonetization and/or the current pandemic situation. The experts have observed that there are many factors that indicate about the problem in the economy. Now consumption and demand has decreased because people want to keep more money with themselves (cash or bank) so that they can meet the sudden and urgent requirements and they are not interested much in spending the money. The decreased consumption has de-motivated the industry and as a result the production has also gone down. The study also finds that how technology can play a role in the helping the economy. It was found that technology can help in cheaper products, providing best services to the customers at affordable prices and provide economical business operations. The sample size of the present study is 244 (122 economists and 144 industry experts). The sampling method was judgment sampling and data analysis tools were weighted mean and multidimensional scaling. Keywords: Economic Slowdown, Multidimensional Scaling, Technology, Cost Effectiveness. JEL Classifications: O3, O47 DOI: https://doi.org/10.32479/ijefi.10460